Roboter für Assistenzfunktionen Konzeptstudien für die Interaktion in der Praxis - Rönnau, Arne; Becker, Pascal; Behnke, Sven (KIT Scientific Publishing, 2024)
The performance and flexibility of robot technologies make it possible to bring robots to everyday life. This creates many challenges: safety, legal regulations, reliability, reusability, and business models must be considered under special conditions. The acceptance and interaction of humans and robots are of central importance for the success of the applications. This collection summarises 15 studies from the BMBF-funded program "Robots for Assistance: Interaction in the Field.